Unraveling the function of TSC1-TSC2 complex: implications for stem cell fate - Shuang Wang; Ruishuang Ma; Chong Gao; Yu-Nong Tian; Rong-Gui Hu; Han Zhang; Lan Li; Yue Li (Stem Cell Research & Therapy)
Abstract Background Tuberous sclerosis complex is a genetic disorder caused by mutations in the TSC1 or TSC2 genes, affecting multiple systems. These genes produce proteins that regulate mTORC1 activity, essential for cell function and metabolism. While mTOR inhibitors have advanced treatment, maintaining long-term therapeutic success is still challenging. For over 20 years, significant progress has linked TSC1 or TSC2 gene mutations in stem cells to tuberous sclerosis complex symptoms. Methods A comprehensive review was conducted using databases like Web of Science, Google Scholar, PubMed, and Science Direct, with search terms such as “tuberous sclerosis complex,” “TSC1,” “TSC2,” “stem cell,” “proliferation,” and “differentiation.” Relevant literature was thoroughly analyzed and summarized to present an updated analysis of the TSC1-TSC2 complex’s role in stem cell fate determination and its implications for tuberous sclerosis complex. Results The TSC1-TSC2 complex plays a crucial role in various stem cells, such as neural, germline, nephron progenitor, intestinal, hematopoietic, and mesenchymal stem/stromal cells, primarily through the mTOR signaling pathway. Conclusions This review aims shed light on the role of the TSC1-TSC2 complex in stem cell fate, its impact on health and disease, and potential new treatments for tuberous sclerosis complex. Graphical abstract